Are Marbling and the Prediction of Beef Eating Quality Affected by Different Grading Sites? - Liu, Jingjing; Pogorzelski, Grzegorz; Neveu, Alix; Legrand, Isabelle; Pethick, David; Ellies-Oury, Marie-Pierre; Hocquette, Jean-François (Frontiers in Veterinary Science, 2021)
For the European abattoirs, the preferred carcass grading site is at the fifth rib, and cutting at the tenth rib as in Australia could lead to a lower economic value of the carcass. Therefore, the objective of this study was to compare the grading scores of marbling and the meat and fat color on Musculus longissimus thoracis et lumborum (LTL) at the fifth and the tenth thoracic vertebrae. The consequences on the prediction of beef eating quality using the Meat Standards Australia (MSA) grading scheme were also evaluated for cull cows, which produce the majority of beef consumed in France. Carcasses from 208 French cattle, mainly Limousine cows, were graded according to the Australian Beef Carcase Chiller Assessment System (ABCAS) used for the implementation of the MSA system. The results indicate that there was no significant difference in the marbling score, between the fifth and the tenth ribs and hence in the MSA index and in the Global Quality [meat quality (MQ4)] scores calculated from marbling values from either the fifth rib or the tenth rib. However, the meat color at the tenth rib was significantly darker than that at the fifth rib (p < 0.01), and the fat color at the tenth rib was significantly yellower than that at the fifth rib (p < 0.001). The results of this study suggest that the grading of marbling can be conducted on M. LTL at the fifth thoracic vertebrae for routine use of the MSA system in France and, more generally, in Europe. However, further investigation and adjustment would be needed for other critical MSA scores (such as rib fat thickness) while respecting the European carcass quartering practices.